Prediction of MSMEs Interest for Halal Certification in Indonesia: Logistic Regression Approach - Elfira Maya Adiba; Faizal Amir (Falah: Jurnal Ekonomi Syariah, 2023)
The existence of regulations on halal certification for all food and beverage products in Indonesia in 2024 has prompted regulators to start inviting MSMEs to register for halal certification. In fact, MSMEs that already have halal certification are still limited. The purpose of this study is to ascertain whether religious affiliation and knowledge of halal regulations might predict or affect MSME interest in halal certification. This research was a quantitative research with data collected from 147 respondents and processed using logistic regression. The results of the study show that religiosity and halal literacy have no effect on the interest of MSMEs to register for halal certification. This research provides benefits to enrich the discourse about the real challenges that occur in the field in implementing halal certification obligations for business actors, especially factors that can encourage them to register their products on halal certification.